PERSEPSI SISWA KELAS IX SMPN 1 SABAK AUH KABUPATEN SIAK TERHADAP PEMBELAJARAN ONLINE (WHATSAPP GRUP) - Zubaidah, Zubaidah; Erlinda, Sri; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract This research was motivated by the awareness that during the Covid-19 pandemic, the world of education underwent changes, where previously learning was carried out in schools and currently learning is done online. When the researchers conducted interviews with several class IX students at SMPN 1 Sabak Auh where there were differences in perceptions about the Perceptions of Class IX students at SMPN 01 Sabak Auh, Siak Regency towards Online Learning Media (Whatsapp Group). The formulation of the problem in this study is "What is the Perception of Class IX Students at SMPN 01 Sabak Auh, Siak Regency towards Online Learning Media (Whatsapp Group)?". This study aims to determine the perception of class IX students at SMPN 01 Sabak Auh, Siak Regency towards Online Learning Media (Whatsapp Group). This research is a descriptive quantitative research instrument in data collection is an interview with 5 questions and a questionnaire. the population in this study were all grade IX students. Where students are taken as a sample of 20 people. Questionnaires were distributed with 23 questions which were distributed directly. Based on quantitative descriptive analysis of data to determine the perception of Class IX students at SMPN 1 Sabak Auh, Siak Regency, on Online Learning Media (Whatsapp Group). Based on the calculation results, it was found that based on the recapitulation of the 2 indicators, the respondents answered Strongly Agree + Agree, namely 18.5% - 85.5% = 67%. The recapitulation results are in category 2 in the range of 50.01% - 75% = Good. Thus, it can be concluded that the perception of Class IX students at SMPN 1 Sabak Auh, Siak Regency towards Online Learning Media (Whatsapp Group) is at a good level. Key Words: Student Perception, Online Learning, (Whatsapp Group).